2012
DOI: 10.1111/cge.12025
|View full text |Cite
|
Sign up to set email alerts
|

First successful double‐factor PGD for Lynch syndrome: monogenic analysis and comprehensive aneuploidy screening

Abstract: Preimplantation genetic diagnosis (PGD) has been applied worldwide for a great variety of single-gene disorders over the last 20 years. The aim of this work was to perform a double-factor preimplantation genetic diagnosis (DF-PGD) protocol in a family at risk for Lynch syndrome. The family underwent a DF-PGD approach in which two blastomeres from each cleavage-stage embryo were biopsied and used for monogenic and comprehensive cytogenetic analysis, respectively. Fourteen embryos were biopsied for the monogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 15 publications
(19 reference statements)
1
19
0
Order By: Relevance
“…In addition to cancer surveillance, carriers of MMR germline mutations can benefit from cancer preventive measures including prophylactic surgeries and preimplantation genetic diagnosis, which will prevent further transmission of the germline mutations to future generations. 13,37,38 Although LS has been extensively characterized in a Western population and the current study is not novel, to the best of our knowledge, the true incidence of LS in Saudi Arabia has not been reported to date. The incidence of LS in all CRC cases in the current study was 0.9%, which is in agreement with incidences reported in earlier studies.…”
Section: Discussionmentioning
confidence: 87%
“…In addition to cancer surveillance, carriers of MMR germline mutations can benefit from cancer preventive measures including prophylactic surgeries and preimplantation genetic diagnosis, which will prevent further transmission of the germline mutations to future generations. 13,37,38 Although LS has been extensively characterized in a Western population and the current study is not novel, to the best of our knowledge, the true incidence of LS in Saudi Arabia has not been reported to date. The incidence of LS in all CRC cases in the current study was 0.9%, which is in agreement with incidences reported in earlier studies.…”
Section: Discussionmentioning
confidence: 87%
“…Several groups have reported the combined use of two or three of these methods in the same embryo to increase precision in the selection of embryos (25)(26)(27). Konstantinidis et al (23) reported a combined procedure of detecting chromosomal abnormality and linkage analysis using the karyomapping method.…”
mentioning
confidence: 99%
“…The aforementioned challenge to select and transfer the embryos with the highest potential to implant leads to the main goal of this work, which is using a specific whole genome amplification (WGA) methodology to develop a clinically reliable DF‐PGD approach to perform monogenic analysis and comprehensive chromosome screening from a single blastomere. The present DF‐PGD approach improves the previously published DF‐PGD strategy where two blastomeres were needed to perform monogenic and cytogenetic diagnoses . This is an affordable methodology that can be performed by any molecular genetics laboratory.…”
Section: Introductionmentioning
confidence: 81%
“…The same WGA product was used for both monogenic and cytogenetic analyses. Monogenic analysis was performed, when possible, using direct and indirect mutation analyses using short tandem repeats, as described elsewhere . For comprehensive cytogenetic assessment, the previously published shortened mCGH protocol was used …”
Section: Methodsmentioning
confidence: 99%